2017
DOI: 10.1016/j.drugpo.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The material, moral, and affective worlds of dealing and crime among young men entrenched in an inner city drug scene

Abstract: A large body of previous research has elucidated how involvement in drug dealing and crime among marginalized urban youth who use drugs is shaped by the imperatives of addiction and survival in the context of poverty. However, a growing body of research has examined how youth’s involvement in these activities is shaped by more expansive desires and moralities. In this paper, we examine the material, moral, and affective worlds of loosely gang affiliated, street level dealing and crime among one group of young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…We observed greater likelihoods of cannabis selling among younger individuals and males, consistent with cohort data from at-risk youth in North America reporting that over half of the participants have engaged in drug dealing, while studies of older PWUD report prevalence estimates of 17-25% (Gwadz et al, 2009;Kerr et al, 2008;Semple, Strathdee, Zians, & Patterson, 2013;Werb et al, 2008). Many PWUD initiate and continue drug dealing despite the associated risks, due to the need to support ongoing drug use, as well as the stigmatization and marginalization that persist as barriers to participation in the legal economy (Fast et al, 2017;Hepburn et al, 2016;Small et al, 2013;Werb et al, 2011). Looking beyond economic explanations, qualitative work suggests that drug dealing can enmesh individuals in valued forms of sociality, morality, dignity and belonging in places characterized by entrenched marginalization and exclusion (Bourgois, 1996;Cheng et al, 2016;Fast et al, 2017;Fast, Shoveller, Shannon, & Kerr, 2010;Wakeman, 2016).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…We observed greater likelihoods of cannabis selling among younger individuals and males, consistent with cohort data from at-risk youth in North America reporting that over half of the participants have engaged in drug dealing, while studies of older PWUD report prevalence estimates of 17-25% (Gwadz et al, 2009;Kerr et al, 2008;Semple, Strathdee, Zians, & Patterson, 2013;Werb et al, 2008). Many PWUD initiate and continue drug dealing despite the associated risks, due to the need to support ongoing drug use, as well as the stigmatization and marginalization that persist as barriers to participation in the legal economy (Fast et al, 2017;Hepburn et al, 2016;Small et al, 2013;Werb et al, 2011). Looking beyond economic explanations, qualitative work suggests that drug dealing can enmesh individuals in valued forms of sociality, morality, dignity and belonging in places characterized by entrenched marginalization and exclusion (Bourgois, 1996;Cheng et al, 2016;Fast et al, 2017;Fast, Shoveller, Shannon, & Kerr, 2010;Wakeman, 2016).…”
Section: Discussionsupporting
confidence: 69%
“…The lowest quasilikelihood under the independence model criterion (QIC) value was used to identify the model with the best overall fit (Pan, 2001). Since engagement with selling illicit drugs has been found to vary by gender and age, and because of strong age and gender correlates of cannabis selling in the preliminary analyses, we also conducted subanalyses to identify predictors of selling cannabis in specific sex and age strata (Bellair & McNulty, 2009;Fast, Shoveller, & Kerr, 2017;Gwadz et al, 2009;Hepburn et al, 2016;Mayock, 2005). These additional models included subgroups of females ≤ 30 years old, males ≤ 30 years old, females > 30 years old, males >30 years old.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reflecting these findings, a recent study from Malmö, Sweden, found that concentrated social disadvantage, residential instability, and numerous alcohol outlets were predictors of violent crime hot spots (Gerell and Kronkvist, 2017). Open illegal drug scenes are associated with violence and burglary as well as drug crimes (Fast, Shoveller, and Kerr, 2017;Sandberg and Pedersen, 2009).…”
Section: The Effect Of Weather On the Spatial Distribution Of Crimementioning
confidence: 99%